2016
DOI: 10.5812/ijp.5016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prevalence of Clinical Consequences of Untreated Dental Caries Using PUFA/pufa Index in a Group of Iranian Children

Abstract: Background: Untreated dental caries have considerable consequences on the growth and development of children and their quality of life. Objectives: The aim of this study was to evaluate the prevalence of clinical consequences of untreated dental caries in a sample of Iranian children based on the pufa/PUFA diagnostic index. Methods: In this descriptive analytical study, 360 students between the ages of 6 -12 years were selected using cluster sampling. Oral clinical examinations were performed by one pedodontis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
2
16
0
4
Order By: Relevance
“…The pufa index was proposed in 2010 by Monse and co-workers to gain data regarding the severity of oral conditions related to untreated caries (Monse et al 2010). Since conception, it has been used successfully with children in a variety of settings including those with limited access to dental care (Baginska et al 2013;Grund et al 2015;Ramazani et al 2017). The 'p' corresponds to pulpal involvement, 'u' for ulceration arising as a result of a carious tooth, 'f' for a fistula and 'a' for a dental abscess.…”
Section: Methodsmentioning
confidence: 99%
“…The pufa index was proposed in 2010 by Monse and co-workers to gain data regarding the severity of oral conditions related to untreated caries (Monse et al 2010). Since conception, it has been used successfully with children in a variety of settings including those with limited access to dental care (Baginska et al 2013;Grund et al 2015;Ramazani et al 2017). The 'p' corresponds to pulpal involvement, 'u' for ulceration arising as a result of a carious tooth, 'f' for a fistula and 'a' for a dental abscess.…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of the oral and dental health status of children, 6-12 years old, indicated that total caries and total prevalence of untreated dental caries in the study population have been 93 and 30%, respectively [16]. The results of a study on 6-11-year-old Indian children revealed that the prevalence of dental caries was 79% in them, with the mean dmft and DMFT of 2.97 and 0.17, respectively [17].…”
mentioning
confidence: 86%
“…Dental caries as the most prevalent infectious disease may affect the child population's health, growth and development (1,2). Accordingly, appropriate dental treatments are required to restore oral and subsequently general health.…”
Section: Dear Editormentioning
confidence: 99%